1989
DOI: 10.1177/0022343389026001004
|View full text |Cite
|
Sign up to set email alerts
|

Internal and External Factors in Effecting Third World Military Expenditures

Abstract: Recent research on the determinants of Third World military expenditures has indicated that economic variables show great promise in providing a framework as to the underlying causes of Third World defense allocation decisions. Building on this research, we test the hypotheses that the level of military expenditures in developing countries is determined in large part by economic constraints relative to external (threat) factors. In general this hypothesis is borne out with the important qualification that coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…A smaller literature focuses on developing countries, which are our primary interest. Deger and Somnath (1991) survey this literature which uses a cross‐sectional approach (see, for example, Maizels and Nissanke, 1986; Looney, 1989; Gyimah‐Brempong, 1989). The dependent variable is the ratio of military spending to GDP, commonly referred to as the ‘defence burden’.…”
Section: Modelling Military Expenditurementioning
confidence: 99%
“…A smaller literature focuses on developing countries, which are our primary interest. Deger and Somnath (1991) survey this literature which uses a cross‐sectional approach (see, for example, Maizels and Nissanke, 1986; Looney, 1989; Gyimah‐Brempong, 1989). The dependent variable is the ratio of military spending to GDP, commonly referred to as the ‘defence burden’.…”
Section: Modelling Military Expenditurementioning
confidence: 99%
“…Recent empirical studies (Looney, 1989Looney and liehay, 1990) have confirmed the importance of economic variLbles in structuring budgetary allocations to the military. One •ariant of this approach stresses the significance of Military Ceynesianism-the use of military expenditures as a counter· yclical tool.…”
Section: Review Of the Literaturementioning
confidence: 97%
“…Rather, this environment is only one of several influences shaping a defense budget, and its effects are filtered or mediated by organizational protocols, institutional processes, a ruling coalition's agenda, and the conditions of the domestic political economy (Cusack and Ward, 1981;Eichenberg, 1992;Harris, 1986;Looney, 1989;Marra, 1985;Ostrom, 1978Ostrom, , 1977Ostrom and Marra, 1986;Rattinger, 1975;Rosh, 1990Rosh, , 1988. Rather, this environment is only one of several influences shaping a defense budget, and its effects are filtered or mediated by organizational protocols, institutional processes, a ruling coalition's agenda, and the conditions of the domestic political economy (Cusack and Ward, 1981;Eichenberg, 1992;Harris, 1986;Looney, 1989;Marra, 1985;Ostrom, 1978Ostrom, , 1977Ostrom and Marra, 1986;Rattinger, 1975;Rosh, 1990Rosh, , 1988.…”
Section: Model Of Arms Races Among Rival Nations Without Modificatiomentioning
confidence: 99%
“…Many studies have shown that defense spending is motivated or constrained by factors other than security concerns (Chan, 1988b;Harris, 1986;Hartley and Sandler, 1990;Looney, 1989;Looney and Frederiksen, 1987;Mintz and Russett, 1992;Mintz and Ward, 1989;Moon and Hyun, 1992;Palmer, 1990;Treddenick, 1985;Ward and Mahajan, 1984). Some have argued that this spending is used as a fiscal stimulus to offset economic downturns, or as a political lever to rally electoral support.…”
Section: Domestic Sources and Consequences Of Defense Spendingmentioning
confidence: 99%